THEORETICAL APPROACHES TO THE CREATION OF PEDAGOGICAL CONCEPTS IN PRESCHOOL EDUCATION (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article presents theoretical approaches to the creation of a pedagogical concept for the implementation of a concept based on certain rules when using modern methods of teaching students in higher education institutions.